Orthopaedic aspect of anatomy and radiology of proximal femur - Suthar, Pokhraj P.; Patel, Chirag D.; Gamit, Manoj; Dave, Dhaval J.; Wadhwani, Chandni; Suthar, Bhumikaben P. (International Journal of Research in Medical Sciences, 2017)
Femoral pathology is common in relation to the orthopedic. There is complex anatomy of the proximal femur and hip joint. So, its knowledge regarding anatomy and radiological correlation is necessary to the well-known fact for the orthopedics for the routine day to day practice. This review article briefly illustrates important anatomical and radiological aspect of the proximal femur.